The equatorial electrojet during geomagnetic storms and substorms - Yamazaki, Yosuke (2015)
He climatology of the equatorial electrojet during periods of enhanced geomagnetic activity is examined using long‐term records of ground‐based magnetometers in the Indian and Peruvian regions. Equatorial electrojet perturbations due to geomagnetic storms and substorms are evaluated using the disturbance storm time (Dst) index and auroral electrojet (AE) index, respectively. The response of the equatorial electrojet to rapid changes in the AE index indicates effects of both prompt penetration electric field and disturbance dynamo electric field, consistent with previous studies based on F region equatorial vertical plasma drift measurements at Jicamarca. The average response of the equatorial electrojet to geomagnetic storms (Dst<−50 nT) reveals persistent disturbances during the recovery phase, which can last for approximately 24 h after the Dst index reaches its minimum value. This “after‐storm” effect is found to depend on the magnitude of the storm, solar EUV activity, season, and longitude.